Disinfection by-products as environmental contaminants of emerging concern: a review on their occurrence, fate and removal in the urban water cycle. Issue 1 (2nd January 2023) - Xiao, Rong; Ou, Tian; Ding, Shunke; Fang, Chao; Xu, Zuxin; Chu, Wenhai
Abstract: Disinfection by-products (DBPs), a kind of secondary pollutant derived from water disinfection treatment, are frequently detected in the urban water cycle and reported to show (eco)toxicological impacts on aquatic systems and human health. Thus, DBPs have become ubiquitous environmental contaminants of emerging concern. This article reviews DBP characteristics as well as DBP occurrence in different aqueous environments, namely reclaimed wastewater, surface water and drinking water. Furthermore, this review discusses research related to the fate and removal of wastewater-derived DBPs and drinking water DBPs in different components of the urban water cycle, including advanced water treatment facilities, natural water systems, drinking water treatment plants, drinking water distribution systems, plumbing systems as well as household water treatment processes. In general, the fate and removal of DBPs in the urban water cycle are under the influence of internal factors (i.e. physicochemical properties and other characteristics of individual DBP) and external factors (e.g., the composition of urban water cycle, treatment conditions of water treatment processes, and the characteristic of water quality). As for future research needs, the identification and monitoring of DBPs as well as the development of predictive models for DBP fate in the urban water cycle are of significance to effectively assess and mitigate the impact of DBPs on ecological safety and human health. Besides, in addition to aquatic system, future research should also pay attention to the occurrence and fate of DBPs in the air and in the terrestrial ecosystem. Graphical abstract: UF0001